2010
DOI: 10.1021/ol100365c
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective, Organocatalytic Reduction of Ketones using Bifunctional Thiourea-Amine Catalysts

Abstract: Prochiral ketones are reduced to enantioenriched, secondary alcohols using catecholborane and a family of air-stable, bifunctional thiourea-amine organocatalysts. Asymmetric induction is proposed to arise from the in situ complexation between the borane and chiral thiourea-amine organocatalyst resulting in a stereochemically biased boronate-amine complex. The hydride in the complex is endowed with enhanced nucleophilicity while the thiourea concomitantly embraces and activates the carbonyl.The enantioselective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 26 publications
4
22
0
Order By: Relevance
“…In addition, other studies have shown that different synthetic catalysts are being used in the reduction of 1-(4-methoxyphenyl)ethanone 1. This alcohol was obtained with good optical purity (96% ee) and excellent conversion (c 98%) by Wang et al (2009), and 97% ee and 80% yield isolated by Li et al (2010). In the present study, we showed that excellent results were achieved in the bioconversion of ketone 1 by several marine-derived fungi.…”
Section: Resultssupporting
confidence: 58%
“…In addition, other studies have shown that different synthetic catalysts are being used in the reduction of 1-(4-methoxyphenyl)ethanone 1. This alcohol was obtained with good optical purity (96% ee) and excellent conversion (c 98%) by Wang et al (2009), and 97% ee and 80% yield isolated by Li et al (2010). In the present study, we showed that excellent results were achieved in the bioconversion of ketone 1 by several marine-derived fungi.…”
Section: Resultssupporting
confidence: 58%
“…Both catalytic systems have been further developed by altering the ligand or by employing different metals in efforts to enhance the selectivity or improve practicality. [3][4][5] Despite extensive research, the utilization of simple chiral Brønsted acids as precatalysts for this asymmetric process is still unknown.…”
mentioning
confidence: 99%
“…Furthermore, the addition of the laser polarimetric detector in series to the UV detector showed the optical activity of the eluted peaks, revealing the elution order in each chromatographic run (Table 2), as showed for compound 2 ( Figure 2). Each of these optical rotation signs can easily be related to a particular AC through literature data 6,[11][12][13][14][15][16] , which allows the full characterization of the sample through the HPLC analysis. This avoids the need for conventional polarimetric measurements and considerably decreases the time to screen the stereoselectivity of new catalyst during the development phase.…”
Section: Resultsmentioning
confidence: 99%